2017
DOI: 10.5430/cns.v5n4p82
|View full text |Cite
|
Sign up to set email alerts
|

Peer buddy mentoring project for nurses’ career development

Abstract: Objective: The aim of the paper is to describe the implementation of a peer buddy mentoring model to support the career development of Registered Nurses (RNs) seeking Clinical Nurse Specialist (CNS) positions. Methods: A qualitative survey design was used to collect data during the workshops, with follow-up semi-structured telephone or face-to-face interviews. Data were also collected via the researchers' notes. Results: A total of 32 participants attended the program and 31 completed the surveys. The particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(24 reference statements)
0
3
0
Order By: Relevance
“… 19 Luck et al found that peer mentoring is a relatively cost-effective strategy requiring minimal resources and negligible disruption to clinical services. 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 Luck et al found that peer mentoring is a relatively cost-effective strategy requiring minimal resources and negligible disruption to clinical services. 33 …”
Section: Discussionmentioning
confidence: 99%
“…19 Luck et al found that peer mentoring is a relatively cost-effective strategy requiring minimal resources and negligible disruption to clinical services. 33 Peer training was found to be a cost-effective method for increasing immunization coverage in health centers. 25 However, the main objectives of a Net percentage gain was calculated from the percentage of mentees who demonstrated correct skills and practices at baseline and endline.…”
Section: Discussion Peer Mentoring: a Nonconventional Effective Learning Approachmentioning
confidence: 99%
“…Although the role of mentoring in nursing has been extensively researched, there is little research in South Africa, on peer mentoring of the critical care nursing student in the critical care environment and its relationship to their learning outcomes. Historically, nurses have supported each other in career advancement, and this has been done through mentorship ( Luck et al , 2017 ). As early as 1970, literature reported stress and anxiety as interrupting learning among nursing students in a clinical learning environment ( Moscaritolo, 2009 ).…”
Section: Literaturementioning
confidence: 99%